Peran Earning Per Share (EPS) dan Deviden Per Share (DPS) Terhadap Harga Saham - Ella Anastasya Sinambela (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The biggest opportunity at investors is the capital market. Various circles are now starting to see stocks as a form of investment in the future. For example, upper class investors, small investors, students, workers, even housewives. Various approaches are taken to anticipate the business world. In the basic approach, the most prominent parameter used is the ratio of EPS and DPS. The most important goal of financial management in any organization is proper expansion. Therefore, a study was conducted to determine the stock price of Earning per Share (EPS) and Dividends per Share (DPS). This study uses data on companies listed on the IDX from 2019-2020. This study used 100 samples. This study uses multiple linear regression analysis, the results show that EPS has a expressive role in the formation of stock prices. Partial results obtained EPS has a expressive force on the formation of stock prices. The same result shows that the share price is also partially affected by dividends per share (DPS)